2021
DOI: 10.13181/mji.oa.215525
|View full text |Cite
|
Sign up to set email alerts
|

Precision health care strategies for older adults with diabetes in Indonesia: a Delphi consensus study

Abstract: BACKGROUND Studies on precision health care for older adults with diabetes in Indonesia are still limited. This study was aimed to reach the experts consensus on the suitable precision health care strategies for older adults with diabetes. METHODS A total of 10 experts (4 physicians, 4 nurses, and 2 dietitians) agreed to participate in the 3-round interview using Delphi technique. The experts should have at least 5 years of experience in teaching or working as health professionals in a hospital. RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Research [31] discussed several efforts devoted to accomplishing precision oncology using big data in Indonesia. Further, study [32] discussed strategies for implementing precision health care in older adults with diabetes in Indonesia. The study concluded that the precision health care strategies for diabetes patients can be broken down into seven phases: doing deductive teaching for a short period of time; assessing the level of self-management and cardiovascular disease risks; arranging a patient brainstorming session to share insights on glycemic targets and specific behavior; generating a list of patients' concerns and prioritizing them; establishing a goal and formulating a plan of action; carrying put follow-up; and keeping track of goal attempts.…”
Section: Literature Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Research [31] discussed several efforts devoted to accomplishing precision oncology using big data in Indonesia. Further, study [32] discussed strategies for implementing precision health care in older adults with diabetes in Indonesia. The study concluded that the precision health care strategies for diabetes patients can be broken down into seven phases: doing deductive teaching for a short period of time; assessing the level of self-management and cardiovascular disease risks; arranging a patient brainstorming session to share insights on glycemic targets and specific behavior; generating a list of patients' concerns and prioritizing them; establishing a goal and formulating a plan of action; carrying put follow-up; and keeping track of goal attempts.…”
Section: Literature Studymentioning
confidence: 99%
“…The study concluded that the precision health care strategies for diabetes patients can be broken down into seven phases: doing deductive teaching for a short period of time; assessing the level of self-management and cardiovascular disease risks; arranging a patient brainstorming session to share insights on glycemic targets and specific behavior; generating a list of patients' concerns and prioritizing them; establishing a goal and formulating a plan of action; carrying put follow-up; and keeping track of goal attempts. Moreover, research [32] shows that there are eight components to precision health care in patients with diabetes: personalized genetic or lifestyle factors, selfmanagement, glycemic target and control, interdisciplinary collaborative practice, patient preferences, patient priority-directed care, and evidence-based practice. Even though there are several studies about precision medicine in Indonesia, the number of continuous research and study is still relatively limited and far from enough to develop precision medicine applications.…”
Section: Literature Studymentioning
confidence: 99%
“…So far, hospital-and community-based interventions in Indonesia to avoid diabetes complications have long been based on evidence-based practice and guidelines for diabetes care [4]. However, more precise intervention for patients with diabetes based on the availability of health data, treatment demands and targets can be executed and imposes challenges in the future [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patient care and preference, patient-oriented, evidence-based care and self-management, referred to precision healthcare [7]. Over time, the approach has been implicated on patients with diabetes and becoming a new trend in clinical settings in developed countries but not really popular in Indonesia [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation